PEMBELAJARAN DARING BERBASIS MULTI APLIKASI UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI PRODI PGMI IAIN PURWOKERTO - Hendri Purbo Waseso (TA'LIM : Jurnal Studi Pendidikan Islam, 2023)
This research departs from the impact of the COVID-19 virus on the world of education. Educational practitioners are forced to adapt to social restrictions. Online learning requires lecturers to master various kinds of online learning applications. The purpose of this study is to find a way out in the implementation of online learning through a combination of various online learning applications so that learning objectives can be achieved. The Kemmis and Taggart action research methods with the stages of planning, observe and act, and reflection are used by researchers as a step to improve learning that is more effective. Data was collected by means of focus group discussions, participatory observation, peer observation and self-assessment. The subjects in this study were 4th semester students of PGMI class A and B at IAIN Purwokerto. The findings in this study are (1) multi-application-based online learning planning is carried out in two cycles. The first cycle uses three learning applications, namely telegram group, google classroom and eclass. While the second cycle uses four applications, namely google meet, google classroom, telegram group and eclass. Each cycle carried out two lessons. The planning process is carried out by compiling technical guidelines for the use of each application in learning that is delivered to students. In addition to technical application use, online lectures based on multi-application technicalities are also prepared; (2) The first cycle found several weaknesses such as low student participation, lecture material could not be captured by students optimally, the dominance of the chat feature on the telegram group application reduced students' motivation to always be online, and three online learning applications still did not support interactive lectures. So that in the second cycle, lectures are carried out using four applications in an integrative way to increase the effectiveness of online learning. The effectiveness is shown in terms of ease, the functionality of the application in each learning activity and the achievement of learning objectives; and (3) The obstacle faced by students in the multi-application-based online learning process is the unstable internet network.